Influence of micellar calcium phosphate on in vitro gastric coagulation and digestion of milk proteins in infant formula model systems. (August 2020) - Huppertz, Thom; Lambers, Tim T.
Abstract: Coagulation of casein micelles in the stomach is an important factor determining gastric transit and digestion kinetics of proteins. The influence of micellar calcium phosphate (MCP) content on the behaviour of milk proteins during in vitro digestion was studied under simulated infant gastric conditions. Samples (1.5% protein, casein:whey protein ratio = 40:60) were prepared using demineralised whey, milk permeate and skimmed milk, from which the MCP content had been adjusted. For milk samples, turbidity decreased and non-sedimentable casein increased with decreasing MCP content. During in vitro gastric digestion, samples prepared with milk with a higher MCP content showed stronger coagulation and these coagulates were found to digest more slowly. SDS-PAGE analysis showed that casein digestion under these conditions was reduced for samples showing stronger coagulation. The outcomes of this study highlight the importance of casein micelle structure and integrity in determining curd formation during in vitro gastric digestion.